Conversion TORS after neoadjuvant immunotherapy for advanced BOT-SCC: a retrospective study - Lin, Quanquan; Zhang, Yingjuan; Sun, Jinlong; Hui, Xiuli; Ren, Yipeng; Song, Zhigang; Wu, Zhiyong; Cai, Boning; Feng, Lin; Zhang, Haizhong; Wang, Feng; Xi, Qing (Frontiers in Oncology, 2026)
IntroductionAdvanced base-of-tongue squamous cell carcinoma (BOT-SCC) has conventionally been regarded as unsuitable for transoral resection owing to its propensity for deep invasion and the difficulty in obtaining adequate surgical margins. We evaluated whether neoadjuvant therapy could enable transoral robotic surgery (TORS) in a subset of patients with advanced BOT-SCC.MethodsIn this retrospective analysis, nine consecutive patients with stage ≥T4N2bM0 BOT-SCC received three cycles of neoadjuvant therapy based on pembrolizumab, followed by TORS with concurrent neck dissection. Radiologic response and tumor shrinkage were assessed after neoadjuvant therapy. Perioperative outcomes, correlations between radiologic shrinkage and operative metrics, postoperative complications (Clavien -Dindo), and 3-month functional outcomes (MD Anderson Dysphagia Inventory [MDADI], Functional Oral Intake Scale [FOIS], and Grade, Roughness, Breathiness, Asthenia, Strain [GRBAS]) were recorded. Follow-up was conducted for oncologic outcomes.ResultsPost-neoadjuvant radiologic evaluation demonstrated clinically meaningful downstaging, with partial response in 6/9 patients (66.7%) and stable disease in 3/9 patients (33.3%). Mean tumor reduction was 35.6% ± 11.2% (median, 36%; interquartile range [IQR], 28 -44). All patients achieved R0 resection. Mean operative time was 193.3 ± 46.9 min (median, 180; IQR, 165 -240), and mean intraoperative blood loss was 78.3 ± 25.4 mL (median, 70; IQR, 60 -100). Tumor shrinkage was inversely correlated with operative time (r = −0.962; 95% CI: −0.992 to −0.825; p < 0.001) and blood loss (r = −0.851; 95% CI: −0.968 to −0.430; p = 0.004), while operative time was positively correlated with blood loss (r = 0.864; 95% CI: 0.469 to 0.971; p = 0.003). No Clavien -Dindo grade ≥III complications or postoperative hemorrhage occurred. At 3 months, functional outcomes were favorable (mean MDADI 75.6 ± 10.2; FOIS ≥6 in 55.6%; median GRBAS 1.1). Over a median follow-up of 12 months, no local recurrences or distant metastases were documented.DiscussionNeoadjuvant therapy may render a subset of patients with advanced BOT-SCC eligible for TORS, enabling oncologically radical resection with low perioperative morbidity and promising early functional recovery. Prospective studies are warranted to validate patient selection criteria and to develop biomarker-guided de-intensification strategies.